Cobalt-based molecular electrocatalysis of nitrile reduction: evolving sustainability beyond hydrogen. Issue 26 (11th June 2019) - Child, Simon N.; Raychev, Radoslav; Moss, Nathan; Howchen, Benjamin; Horton, Peter N.; Prior, Christopher C.; Oganesyan, Vasily S.; Fielden, John
Abstract : Two complexes, designed as hydrogen evolution catalysts, are shown to be the first earth-abundant molecular electrocatalysts for reduction of acetonitrile to ethylamine. Abstract : Two new cobalt bis-iminopyridines, [Co(DDP)(H2 O)2 ](NO3 )2 (1, DDP = cis -[1, 3-bis(2-pyridinylenamine)] cyclohexane) and [Co( cis -DDOP)(NO3 )](NO3 ) (2, cis -DDOP = cis -3, 5-bis[(2-Pyridinyleneamin]- trans -hydroxycyclohexane) electrocatalyse the 4-proton, 4-electron reduction of acetonitrile to ethylamine. For1, this reduction occurs in preference to reduction of protons to H2 . A coordinating hydroxyl proton relay in2 reduces the yield of ethylamine and biases the catalytic system back towards H2 .